Implementation of a Learning Experience Platform with Counseling Professionals: A Proposal from an Active Learning Approach - VILLALOBOS BENAVIDES, VICTOR (2024)
This article analyzes the learning experience through the use of a learning experience platform for continuous training processes among members of the Association of Orientation Professionals.  The study was conducted with 13 members of the association using a socio-critical methodology and a participatory research design. A technopedagogical design was elaborated based on the diagnostic, design, implementation and evaluation phases of the experience, and was developed through a course incorporated in the Professional Development Program that strengthens socioemotional attention in educational environments. The results show that the Perusall® platform is able to integrate characteristics of the active learning approach. The conclusions highlight the need to develop proposals focused on personalized learning environments, and the Learning Experiences Platform (LXP) is an innovative pedagogical tool that combines recent technologies. The design of Technical Pedagogical Content Knowledge (TPACK) favors strategic and agile planning in the elaboration of didactic proposals and identifies desirable characteristics for future training processes based on the proposed approach, such as greater socio-collaborative spaces, theoretical-practical link with work environments and deepening of critical thinking.